Research Trend on Business Innovation Using Bibliometric Analysis with VOSviewer - Dika Putra Wijaya; Mohammad Kawtsar; Manon Guiny; Ganesh Ganesh; Nur Laila; Wirda Amirotul Amiroh (International Journal of Kita Kreatif, 2026)
This study aims to map global research trends and identify dominant thematic clusters within the business innovation literature to provide a comprehensive structural framework. Using a descriptive bibliometric approach, publication data spanning from 2022 to 2026 was retrieved from a premier scientific database to evaluate emerging literature patterns and keyword linkages. The findings reveal three core thematic clusters internal dimensions, organizational outcomes, and macro contexts with "business model" and "performance" acting as the central anchors of current academic discourse. Temporally, the literature exhibits a significant evolutionary shift from theoretical foundations in late 2023 toward contemporary, practical applications of digital and green innovation by mid-2024. A key limitation of this study stems from its data scope being bounded to a single scientific database; however, its practical implications highlight that integrating digital and environmental strategies is vital for long-term competitiveness and agility in volatile markets. The distinct novelty of this research lies in providing an integrated Data-Driven Sustainable Business Model Innovation (DDSBMI) perspective, systematically uncovering how technological and ecological factors interact within the broader innovation ecosystem rather than analyzing variables in isolation.